Larvicide activity of the alkaloids base of the dry leaves of Croton conduplicatus Kunth - Estrada Reyes, David José; Márquez Vizcaíno, Rita Luz; Jaramillo Salazar, María Cristina (Revista Productos Naturales, 2022)
This research aimed to evaluate the larvicidal activity of the alkaloidal base of the dried leaves of Croton canduplicatus on Aedes aegypti‚ vector of viruses that cause diseases of serious epidemiological impact‚ social and economic such as dengue‚ yellow fever, chikungunya and zika.
Keywords: Croton canduplicatus; Aedes aegypti; aporphine alkaloid